EFFECT OF THE EQUIPMENT CAPTURE VALVES TRAP BASIS OF CATCH IN THE VILLAGE OF BATU BELUBANG DISTRICT SENAYANG DISTRICT LINGGA RIAU ISLANDS PROVINCE - Umi Kalsum; Irwandy Syofyan; Nofrizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study was conducted in May 2014 held at the village of Batu Belubang Senayang District of Lingga District Riau Islands Province. The purpose of this study is to find the right form valves or better to be used by fishermen. This study uses three treatments, namely: valves the shape pointing up, valves whose shape pointing downward, and valves that looks straight ahead. The method used in this study is the experimental method, the entire unit of experiments carried out in the field. From this results, the catch valves leads down better than the catch valves pointing up and straight forward, both in the amount of weight (kg) and in the number of individuals (tail). Basic trap catches with all three forms of the valves dominated by domersal and carnivorous fish.Key words :